Use of immunohistochemical analysis of CK5/6, CK14, and CK34betaE12 in the differential diagnosis of solid papillary carcinoma in situ from intraductal papilloma with usual ductal hyperplasia of the breast. (November 2018) - Maeda, Ichiro; Tajima, Shinya; Kanemaki, Yoshihide; Tsugawa, Koichiro; Takagi, Masayuki
Objectives: The aim of this study was to use immunohistochemistry to differentiate solid papillary carcinoma in situ from intraductal papilloma with usual ductal hyperplasia (IPUDH). Three types of high-molecular-weight cytokeratins (CKs) – CK5/6, CK14, and CK34betaE12 – were targeted. Methods: We studied 17 patients with solid papillary carcinoma in situ and 18 patients with IPUDH diagnosed by at least two pathologists. Immunohistochemical analyses used antibodies to CK5/6, CK14, and CK34betaE12 to make the differential diagnosis of solid papillary carcinoma in situ versus IPUDH. Immunohistochemical staining was scored as 0–5 using Allred score. Results: Immunohistochemistry with CK5/6 and CK14 antibodies produced scores of 0–3 in all patients with solid papillary carcinoma in situ and 2–5 in all patients with IPUDH. Immunohistochemical staining with CK34betaE12 antibody produced scores of 1–3 in all patients with solid papillary carcinoma and 3–5 in all patients with IPUDH. In tissues from patients with IPUDH, significantly more cells were stained with CK34betaE12 than CK5/6 ( p  < 0.05) or CK14 ( p  < 0.05). Conclusion: The immunoreactivity of CK5/6, CK14, and CK34betaE12 antibodies was useful to differentiate solid papillary carcinoma in situ from IPUDH. CK34betaE12 is especially useful for distinguishing solid papillary carcinoma from IPUDH.